Abandoning creativity: The evolution of creative ideas in engineering design course projects. (November 2016) - Starkey, Elizabeth; Toh, Christine A.; Miller, Scarlett R.
Abstract : Creativity training has been widely integrated into engineering education as a means to prepare students to be an innovative force in design industry. However, much of this research has focused on training students to be creative idea generators, with limited attention to what happens after this generation. Thus, the current study was developed to understand how creative ideas are promoted or filtered throughout the design process in order to focus our educational efforts. In order to accomplish this, an 8-week study with 136 engineering students was conducted. Our results point to the reduction in creativity throughout the design process and student abandonment of novel concepts. We also expose the influence of the design task on student creativity. Highlights: Creativity in engineering education is impacted by the design task being explored. Students discard novel ideas during concept selection for conventional alternatives. Creativity during generation and selection does not predict final design creativity.